THE QUALIFICATIONS OF MEDIATORS IN CIVIL MATTERS, INCLUDING EMPLOYMENT DISPUTES, IN POLAND AND ROMANIA - Antolak-Szymanski, Katarzyna; Cărăbaş, Mihai (Review of European and Comparative Law, 2023)
Mediation is increasingly promoted as an effective means of dispute resolution within the European Union, especially in civil cases. However, in Member States that lack a strong tradition of mediation, such as Poland and Romania, mediation has developed slower than expected. In this paper, the authors argue that one reason for this may be the lack of qualified mediators for civil and employment cases in both countries. They claim that legislators should enact higher qualification standards, including requiring specialized knowledge and ensuring that mediator certification is not outsourced to private mediation organizations with low-quality training programs.